Interactions between Age, Sex, and Hormones in Experimental Ischemic Stroke - Liu, Fudong (2012)
Age, sex, and gonadal hormones have profound effects on ischemic stroke outcomes, although how these factors impact basic stroke pathophysiology remains unclear. There is a plethora of inconsistent data reported throughout the literature, primarily due to differences in the species examined, the timing and methods used to evaluate injury, the models used, and confusion regarding differences in stroke incidence as seen in clinical populations versus effects on acute neuroprotection or neurorepair in experimental stroke models. Sex and gonadal hormone exposure have considerable independent impact on stroke outcome, but these factors also interact with each other, and the contribution of each differs throughout the lifespan. The contribution of sex and hormones to experimental stroke will be the focus of this review. Recent advances and our current understanding of age, sex, and hormone interactions in ischemic stroke with a focus on inflammation will be discussed.